2014
DOI: 10.1182/asheducation-2014.1.565
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T lymphocytes for leukemia and lymphoma

Abstract: This chapter focuses on the recent advances in adoptive T-cell immunotherapies, not only for patients after hematopoietic stem cell transplantation, but also in the autologous setting using T cells early in the disease process for the treatment of the highest-risk patients with leukemias and lymphomas. The particular emphasis is to highlight the role of T-cell therapies for hematologic malignancies using a non-gene-transfer approach to direct specificity, including the clinical use of T-cell therapies for EBV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Polyclonal, virus-specific T cells expanded ex vivo and reinfused into hematopoietic stem cell transplant patients have shown efficacy for the treatment of Epstein-Barr virus (EBV), cytomegalovirus (CMV), adenovirus, BK virus, and human herpesvirus 6 infection [28][29][30][31][32][33][34] as well as the treatment of EBV-mediated malignancies. [35][36][37][38][39] T cells generated using these sophisticated methods of expansion have been safe and well tolerated, as well as highly effective. 38,40 We previously demonstrated that it is feasible to adapt this method of expansion of polyclonal virus-specific T cells to the HIV setting and expand polyfunctional, potent HXTCs targeting multiple HIV epitopes under good manufacturing practice (GMP) conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Polyclonal, virus-specific T cells expanded ex vivo and reinfused into hematopoietic stem cell transplant patients have shown efficacy for the treatment of Epstein-Barr virus (EBV), cytomegalovirus (CMV), adenovirus, BK virus, and human herpesvirus 6 infection [28][29][30][31][32][33][34] as well as the treatment of EBV-mediated malignancies. [35][36][37][38][39] T cells generated using these sophisticated methods of expansion have been safe and well tolerated, as well as highly effective. 38,40 We previously demonstrated that it is feasible to adapt this method of expansion of polyclonal virus-specific T cells to the HIV setting and expand polyfunctional, potent HXTCs targeting multiple HIV epitopes under good manufacturing practice (GMP) conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, not only CD8+ tumor-reactive T cells are isolated with this approach, but also effector CD4+ CTLs. Although CD4+ T cells are classically viewed as helper cells facilitating CD8+ T cell function, it is now clear that both cell subsets can exert cytotoxicity against tumor targets ( 3 , 38 ). Moreover, we have demonstrated that by sorting doublet-forming T cells, we are selecting only cytotoxic T cells and depleting regulatory T cells with immune suppressive function from the pool of patient's T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the expression of TLR2 significantly increased following stimulation with rMBP-NAP, which indicated that the secretion of antitumor cytokines from PBMCs possibly depend on the TLR2 signaling pathway. Cytotoxic lymphocytes, which serve an essential role in cancer immunotherapy, have been identified as CD4 + CTL and CD8 + CTL (29). The CD4 + CTLs produce multiple antitumor cytokines, including INF-γ, and facilitate CD8 + T cell activation and differentiation (30).…”
Section: Discussionmentioning
confidence: 99%